2019
DOI: 10.1177/1753425919853333
|View full text |Cite
|
Sign up to set email alerts
|

The novel polyclonal Ab preparation trimodulin attenuates ex vivo endotoxin-induced immune reactions in early hyperinflammation

Abstract: Sepsis is a syndrome associated with excessive inflammation. Since mortality from sepsis remains high, more laboratory research is needed to provide insight into more effective ways to use novel, potentially more beneficial agents in sepsis. We investigated the ex vivo immunomodulatory effect of a novel polyclonal Ab preparation, trimodulin, containing IgM (∼23%), IgA (∼21%) and IgG (∼56%). Using whole blood and purified PBMCs from healthy volunteers and patients with sepsis, various ex vivo investigations upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
(87 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, a recent clinical study in patients treated with either IgM and IgA enriched immunoglobulin or placebo (NaCl) showed a significant decrease of IL-6 and IL-10 levels at 72 h in the IgM and IgA enriched immunoglobulin group only [74]. Ex vivo data also showed that the investigational preparation, trimodulin, lowered monocyte expression of recognition receptors (TLR2 and TLR4) and coagulation receptors (CD11b and CD64) and also reduced lymphocyte proliferation and release of pro-and anti-inflammatory cytokines including TNF-α and IL-10 [83]. Recently, a beneficial effect of IgM administration on microvascular perfusion parameters could be demonstrated in humans [74], which corroborated earlier research in an animal model of endotoxemia [84].…”
Section: Why Focus On Immunoglobulins?mentioning
confidence: 87%
“…Furthermore, a recent clinical study in patients treated with either IgM and IgA enriched immunoglobulin or placebo (NaCl) showed a significant decrease of IL-6 and IL-10 levels at 72 h in the IgM and IgA enriched immunoglobulin group only [74]. Ex vivo data also showed that the investigational preparation, trimodulin, lowered monocyte expression of recognition receptors (TLR2 and TLR4) and coagulation receptors (CD11b and CD64) and also reduced lymphocyte proliferation and release of pro-and anti-inflammatory cytokines including TNF-α and IL-10 [83]. Recently, a beneficial effect of IgM administration on microvascular perfusion parameters could be demonstrated in humans [74], which corroborated earlier research in an animal model of endotoxemia [84].…”
Section: Why Focus On Immunoglobulins?mentioning
confidence: 87%
“…A polyclonal antibody preparation designated trimodulin, which contains IgM (~23%), IgA (~21%), and IgG (~56%), decreases the levels of TLR2, 4 as well as those of coagulation receptors (CD11b and CD64) in monocytes and inhibits lymphocyte proliferation and regulate of the production of pro-and antiinflammatory cytokines, including TNF-a and IL-10. Therefore, these antibodies achieve a protective effect to alleviate the inflammatory reaction to target organs through these extents of involvement in immune system (243,246,247,(250)(251)(252).…”
Section: Role Of Igm Antibodymentioning
confidence: 99%
“…Significantly, in addition to the potential induction of immune tolerance of humoral immunity-associated components to transplanted grafts (35,243,247,248,(250)(251)(252), AIM and IgMenriched IVig have a tissue repair and regeneration effect through the clearance of injured tissue (42,224,(233)(234)(235). Therefore, humoral immunity associated injury after the onset of AMR, which was considered irreversible, could be recovered by clinical application of these humoral immunity-associated components.…”
Section: Clinical Potential Of Humoral Immunity-associated Components In Amrmentioning
confidence: 99%
“…Previous investigations address desirable effects on the well-known effector functions of IgG and IgM [ 23 , 25 , 26 , 27 , 28 , 36 ]. In contrast, some other work—focused on plasma-derived IgA—demonstrate promising anti-pathogenic and immunomodulatory effects of IgA by the interaction with FcαRI [ 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%